Socio-economic factors related to moral reasoning in childhood and adolescence: the missing link between brain and behavior - Caravita, Simona Carla Silvia; Giardino, Simona; Lenzi, Leonardo; Salvaterra, Mariaelena; Antonietti, Alessandro (Frontiers in Human Neuroscience, 2012)
Neuroscientific and psychological research on moral development has until now developed independently, referring to distinct theoretical models, contents and methods. In particular, the influence of socio-economic and cultural factors on morality has been broadly investigated by psychologists but as yet has not been investigated by neuroscientists. The value of bridging these two areas both theoretically and methodologically has, however, been suggested. This study aims at providing a first connection between neuroscientific and psychological literature on morality by investigating whether socio-economic dimensions, i.e. living socio-geographic/economic area, immigrant status and SES, affect moral reasoning as operationalized in moral domain theory (a seminal approach in psychological studies on morality) and in Greene and colleagues’ (2001) perspective (one of the main approaches in neuroethics research). Participants were 81 primary school (M = 8.98 yrs.; SD = 0.39), 72 middle school (M = 12.14 yrs.; SD = 0.61) and 73 high school (M = 15.10 yrs.; SD = 0.38) students from rural and urban areas. Participants’ immigrant status (native vs. immigrant) and family SES level were recorded. Moral reasoning was assessed by means of a series of personal and impersonal dilemmas based on Greene and colleagues' (2001) neuroimaging experiment and a series of moral and socio-conventional rule dilemmas based on the moral domain theory. Living socio-geographic/economic area, immigrant status and SES mainly affected evaluations of moral and, to a higher extent, socio-conventional dilemmas, but had no impact on judgment of personal and impersonal dilemmas. Results are mainly discussed from the angle of possible theoretical links and suggestions emerging for studies on moral reasoning in the frameworks of neuroscience and psychology.